Study on the Meshing Performance of a Spur Gear Pair with Parametric Modification - Shen Xingquan; Zhang Jinchang; Chen Zhenya (Jixie chuandong)
The modification design based on parametric gear model can improve the meshing performance rapidly and effectively. Parametric tooth profile and tooth helix modification of the fully parametric spur gear are carried out in the UG. The finite element simulation is performed by using Hypermesh and Workbench to obtain the gear meshing characteristics under different conditions. The simulation results show that for the same working condition,choosing the proper method of modification and modification parameters can obviously improve the meshing effect. At the same time,through the gear bench test,comparing the gear vibration data before and after modification,it is found that the gear vibration performance of the modified gear are obviously better than that of the unmodified gear. By analyzing the results of simulation and experiments,the modification of tooth axial of drum shape has a better effect on the partial load of tooth flanks and the profile modification has a significant effect on the improvement of load distribution between teeth. The optimum modification method and the amount of modification can quickly obtained by the parametric modification of gear which short the R & D cycle and provide an important theoretical reference for practical engineering.